BP Reduction by Renal Denervation Maintained over 24 Months in the EnligHTN I Trial - Nichols, Emma Hitt (MD Conference Express, 2014)
The EnligHTN renal denervation system reduced office blood pressure (BP) with no serious periprocedural adverse events over 24 months of follow-up. This article presents long-term data from the first-in-human Safety and Efficacy Study of Renal Artery Ablation in Resistant Hypertension Patients trial [EnligHTN I; NCT01438229].